2019
DOI: 10.1590/1808-1657000922017
|View full text |Cite
|
Sign up to set email alerts
|

Synanthropic diptera affecting layer poultry farms: a review

Abstract: The poultry farm of posture is an economic activity of great relevance to Brazil. Health aspects of flocks of laying chickens, such as the occurrence of infestations by parasites and poultry pests, influence significantly the productivity indicators. In this context, the control of synanthropic diptera is one of the challenges of the poultry farmers and professionals of this area. In Brazil, the control of flies in poultry environments is based mainly on the use of pesticides, while other alternatives are less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It was found that hen houses that perform manual removal of manure or tend to leave it below the cage for a longer time period use acaricides more frequently to control these ectoparasites. However, farms that periodically remove the manure or do so through manure conveyor belt do not useacaricide (OLIVEIRA et al, 2018;REZENDE et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that hen houses that perform manual removal of manure or tend to leave it below the cage for a longer time period use acaricides more frequently to control these ectoparasites. However, farms that periodically remove the manure or do so through manure conveyor belt do not useacaricide (OLIVEIRA et al, 2018;REZENDE et al, 2019).…”
Section: Resultsmentioning
confidence: 99%